The Importance of Regular Pc Maintenance to Avoid Damage - Sulastri Eksan; Kenneth Kivael Tamale; Mackenzie G. Repi; I Dewa Gede Septian Arta; Phoebe Fortunella Tumewu (Syntax Corporation Indonesia, 2025)
Computers are essential devices in various activities, including work and education. However, the lack of regular maintenance can lead to decreased performance and even permanent damage. This study aims to analyze the impact of regular maintenance on the lifespan and performance of computer systems. The research method used is an experimental study comparing two groups of PCs: one with regular maintenance and the other without. The results show that computers undergoing routine maintenance experience a performance efficiency increase of up to 30% and a longer lifespan compared to those without maintenance. Further discussion highlights the importance of hardware cleaning, software updates, and storage management in maintaining system stability. In conclusion, regular PC maintenance is a crucial step in preventing damage and improving both performance and device longevity.